1980
DOI: 10.7326/0003-4819-92-2-243
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effective Care of End-Stage Renal Disease: A Billion Dollar Question

Abstract: We examined the survival time and costs of therapy for patients with end-stage renal disease. A computer simulation model of the current system was constructed to estimate the cost-effectiveness of home and center hemodialysis and live related as well as cadaver donor renal transplantation. Analysis of the simulation showed that live related donor transplantation was the least costly and had the greatest survival time, while center hemodialysis had the poorest cost-effectiveness. By simulating changes to the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…Live related renal transplantation is established as the most cost-effective treatment for ESRF [21]. The survival of transplants from living donors is significantly better than cadaveric transplants [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Live related renal transplantation is established as the most cost-effective treatment for ESRF [21]. The survival of transplants from living donors is significantly better than cadaveric transplants [22].…”
Section: Discussionmentioning
confidence: 99%
“…Data acquisition is speeded up by using a parallel imaging SENSE factor of 1.2. The following parameters were used: TR/TE55.9/2.7 ms, 85 u flip angle, voxel size 0.660.660.8 mm, TFE factor of 44, two signal averages and a bandwidth of 769 Hz pixel 21 . The acquisition sequence includes a slice selective inversion pulse with an inversion delay time of 325 ms, spectral pre-saturation with inversion-recovery (SPIR) fat suppression, and a regional saturation technique slab to suppress signal from the inferior vena cava, renal vein and intestines.…”
Section: Mr Data Acquisitionmentioning
confidence: 99%
“…They concluded that transplantation was always less expensive than hemodialysis. Although, in a strict cost analysis, ECD kidney recipients take longer to reach the break-even point and this point might not be reached consistently if allograft survival proved to be dramatically reduced in some patient cohorts, in general, utilization of DCD and ECD kidneys is still a cost-saving treatment strategy when compared to hemodialysis (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…While there has been much activity there particularly on system utilization, policy decision support and public health, 3 limited evidence of implementation exists. [3][4][5][6] An example to demonstrate the potential, however, is presented by Roberts et al, 7 where it is reported that by simulating changes to the current care pathway of end-stage renal disease, shifts from medical center dialysis to either home dialysis or cadaver donor transplantation would save US$284 million per year. The literature demonstrates the application of different simulation methods-mostly Monte Carlo simulation, discrete event simulation, system dynamics (SD), and agent-based simulation-in healthcare.…”
Section: Introductionmentioning
confidence: 99%